IS P2P LENDING EMERGING AS A NEW THREAT TO BANK CREDITS? - Stanley, Nicklaus; Kohardinata, Cliff; Widianingsih, Luky Patricia; Junianto, Yopy; Ismawati, Anastasia Filiana; Sari, Evi Thelia (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2024)
The emergence of fintech is one of the newest business models in the financial sector. One of fintech’s service products is P2P platforms. Since the P2P platform first emerged, it has experienced drastic and significant changes. The banking sector, which distributes credits to consumers in the form of working capital credit, consumption credit, and investment credit, has a major contribution to Indonesia’s economic growth and must be cautious of the significant growth of P2P lending. This empirical study aims to examine the impact of P2P lending on working capital credit, consumption credit, and investment credit in Indonesia throughout 2022. This empirical study uses secondary data obtained from the Financial Services Authority (OJK) website from January 2022 to December 2022which is then analyzed using panel data regression. The results of this empirical study show that P2P lending does not significantly affect working capital credit and investment credit, but instead has a significant positive effect on consumption credit.